2014
DOI: 10.1136/bmjopen-2013-004631
|View full text |Cite
|
Sign up to set email alerts
|

Youth tobacco access: trends and policy implications

Abstract: ObjectiveWe examined whether the supply routes via which New Zealand adolescents aged 14–15 years accessed tobacco had changed during a period of dynamic policy activity.SettingWe analysed data from seven consecutive years (2006–2012) of the New Zealand Action on Smoking and Health (ASH) Year 10 survey, a nationwide cross-sectional annual survey.ParticipantsAll New Zealand schools teaching Year 10 students are invited to participate in the survey; school-level participation rates have ranged between 44% and 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…However, there are encouraging signs that regulatory measures and changing social norms may be able to reduce this access. A recent New Zealand study showed that friends are becoming less important as a source for cigarettes,70 indicating that both general reductions in prevalence and targeted interventions informed by qualitative research are likely to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are encouraging signs that regulatory measures and changing social norms may be able to reduce this access. A recent New Zealand study showed that friends are becoming less important as a source for cigarettes,70 indicating that both general reductions in prevalence and targeted interventions informed by qualitative research are likely to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…For analysis, as in previous studies,22 23 we combined categories 1 and 2 (commercial source), 3 and 4 (friend source), 5 and 6 (parental source), and 7 and 8 (other source). We focused on the commercial source of supply, since the POS display ban potentially most directly affected this supply route.…”
Section: Methodsmentioning
confidence: 99%
“…ways for cannabis procurement. Based on experiences with alcohol and tobacco or even prescription (e.g., opioid) pharmaceuticals used nonmedically, it can be expected that these indirect ways will likely remain the main ways of Page 14 of 27 A c c e p t e d M a n u s c r i p t 14 procurement (Gendall, Hoek, Marsh, Edwards, & Healey, 2014;Ogilvie, Gruer, & Haw, 2005;Schepis & Krishnan-Sarin, 2009). While this is not ideal from the perspective of public health-oriented policy including the best possible protection of young people's well-being and safety, it is more desirable than predominant or inevitable black market engagement, which is the current status quo, and which may actively facilitate exposure to other illicit drugs or drugs which are less likely to be quality-controlled.…”
Section: The Impact Of Legalization On Black Marketsmentioning
confidence: 98%